Paul and the Jewish law : halakha in the Letters of the Apostle to the Gentiles - Tomson, Peter J., 1948- (Compendia Rerum Iudaicarum ad Novum Testamentum, 1990)
While interest in Paul's relationship to Judaism has been growing recently, this study adds an important aspect by comparing Paul's practical instruction with the ancient halakha or Jewish traditional law. First Corinthians is found to be a source of prime importance, and surprisingly, halakha appears to be basic to Paul's instruction for non-Jewish Christians. The book includes thorough discussion of hermeneutic and methodological implications, always viewed in relation to the history of Pauline and Judaic study. Attention is also being paid to the setting within Hellenistic culture. Finally, conclusions are drawn about the texture of Paul's thought and these are applied to two 'theological' passages decisive for his place in Judaism. Historical and theological implications are vast, both regarding Paul's relationship to Judaism, his attitude towards Jesus and his Apostles, and the meaning of his teaching concerning justification and the Law.